Coexistent Uterine Myoma, Colon Adenocarcinoma Ureteral Duplication in A Young Female Patient (Annals of Medical Research, 2021)
None
Keywords: Leiomyoma Uteri, Ureteral Duplication, Colorectal Carcinoma.